Modified ultra high-performance concrete with boron carbide for neutron and gamma radiation shielding - Ramli, Nurhayati; Muhammad Rashid, Raizal Saifulnaz; Mohd Nasir, Noor Azline; Voo, Yen Lei; Masenwat, Noor Azreen; Abdul Karim, Julia (Elsevier, 2025)
Four Ultra High-Performance Concrete (UHPC) modified mixes were studied with 0%, 5%, 10%, 15%, and 20% of boron carbide as aggregates replacement for silica sand denoted as UREF, UBC5, UBC10, UBC15, and UBC20, respectively. Overall, as the boron carbide content increases, workability decreases while density improves. The UBC20 mix showed a 14.77% reduction in compressive strength compared to the UREF. Nonetheless, the compressive strength still exceeded 140 MPa at 28 days. Boron carbide demonstrated better radiation shielding where the shielding capability for the UBC20 mix shielded gamma and neutron was 16.89% with 60Co source, 5.23% with 137Cs source, as well as 37.48% with neutron source, respectively, better than the UREF specimen. These findings demonstrate that increasing boron carbide content progressively enhances the shielding properties of the concrete. However, caution is advised with higher boron carbide inclusion, as it may significantly reduce strength.